Organizational trust, risk and creativity - Rodrigues, Filipa (2013)
The competitiveness has guided companies to an investment in creativity as a means of innovation. Organizational trust has a positive impact in organizations, leading to an increase in cooperation, creativity and innovation. We start with the question: can trust in leadership inluence the behaviour of employees to risk more new ideas? 244 employees of diferent functional arear and levels of work seniority participated in this study. We detected that there is a positive relationship between trust and behaviour to provided new ideas. Employees from nonproductive areas have higher levels of trust in leadership and as such take more risks in creating new ideas, than direct employees.